Does contract farming enhance farm efficiency? A case of wheat growers of Haryana, India - Saroj; Kirtti Ranjan Paltasingh; Pabitra Kumar Jena (Heliyon, 2023)
This study tries to evaluate the returns to contract farming (CF) in the form of farm efficiency for both contract and non-contract wheat growers in Haryana, North India. Applying the data envelopment analysis and endogenous switching regression model on cross-sectional survey data from 754 wheat farmers, it finds that CF adopters are significantly more efficient than non-adopters. Further, it reveals that farmers who adopt CF would reduce their technical efficiency by 16% if they do not participate in it. But non-adopters would increase their technical efficiency by 12% if they adopt instead. This is attributed to CF provisions of higher quality inputs and improved production technology. However, results also indicate that a small percentage of farmers are dealing with some financial constraints, including delayed payment, high cost of inputs, and lack of timely access to financial assistance. This needs to be addressed adequately in order to enfold the smallholders in the ambit of contracting system.